Trends in Pneumonia and Influenza-associated Hospitalizations in South Korea, 2002-2005 - Kim, Soon Ae; Kilgore, Paul E; Lee, Sang-Yi; Nyambat, Batmunkh; Ki, Moran (Journal of Health, Population and Nutrition, 2012)
Pneumonia and influenza are leading causes of morbidity and mortality across the globe. Korea has established the national health-insurance system to cover the entire Korean population since 1989. The aim of this study was to describe the epidemiologic trends in pneumonia and influenza-associated hospitalizations and deaths using the Korean National Health Insurance databases and national vital statistics. During 2002-2005, 989,472 hospitalizations and 10,543 deaths due to pneumonia and influenza were recorded. Eighty-one percent of the hospitalizations were related to diagnoses with unspecified aetiology. The average annual rate of hospitalizations due to pneumonia and influenza was 5.2 per 1,000 people [95% confidence interval (CI) 5.2-5.3], and the hospitalization rate increased by 28% (from 4.5 to 5.8 per 1,000 people) during the four-year study period. In addition, deaths due to pneumonia and influenza increased by 48% (2,829 during 2003, 3,522 during 2004, and 4,192 during 2005). Overall, the national burden of hospitalizations and deaths due to pneumonia and influenza in Korea was high, and it increased for all age-groups during the study period. A comprehensive review of potential interventions by the government authorities should aim to reduce the burden of pneumonia and influenza. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9894 JHPN 2011; 29(6): 574-582